“KORUPSI SEJARAH” DALAM ISLAM - Edi Susanto Edi Susanto (Karsa: Journal of Social and Islamic Culture)
AbstractThis article tries to show that the internal conflicts among  the ummah have broken since  the   early  period  of Islam. The critical study of early Islamic period  to uncover the historical distortions was regarded dangerous  and painful .  A critical study of  this early period will give us a new description of this period based on a strong data; and this critical history leads us to realize that such critical study will not violate the sacredness of Islam..Kata-kata kuncikorupsi sejarah, al-Khulafa’ al-Rasyidun, Dinasti Umayah, Dinasti Abbasiyah